Diverticulum of the midthoracic oesophagus and left diaphragmatic relaxation - Antonacci, Nicola (BMJ Publishing Group, 2010)
The case of a 58-year-old man with a large midthoracic oesophageal diverticulum and a left diaphragmatic relaxation who presented with night regurgitations, abdominal bloating, epigastric burning and a sensation of fullness after meals is reported. The patient underwent a successful thoracotomic diverticulectomy with left diaphragmatic plicature. The postoperative course was uneventful. To our knowledge this is the first reported case of an association between midthoracic oesophageal diverticulum and left diaphragmatic relaxation. Moreover, we hypothesised that the diverticulum was caused by a pulsion mechanism due to obstruction of the distal oesophagus secondary to diaphragmatic relaxation.